APPLICATION OF THE YANBU'A METHOD IN IMPROVING MADRASAH STUDENTS' AL-QUR'AN READING SKILLS - Prayitno, Rifka Fitrizia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The Yanbu'a method is a learning method that is equipped with the selection of reading learning materials and delivery techniques to students in a very simple, effective and universal manner. This method is expected to be able to improve students' Al-Qur'an reading skills. The approach used in this research uses a qualitative approach with a case study type. A case study is an exploration of a bound system or a case over time through in-depth and detailed data collection involving multiple sources of information with rich context. The research analyzed data in 3 stages. The three stages of data analysis techniques are data reduction or condensation, presenting data or showing information, and drawing conclusions or making decisions from the various information obtained. The aim of this research is to equip students to be able to read and understand the Al-Qur'an fluently and correctly, to be able to study the Al-Qur'an as early as possible, to correct mistakes and perfect what is lacking.